Male nudity and trauma in Marc Recha's Pau i el seu germà and Dies d'agost. Issue 2 (June 2019) - Pujol, Anton
Abstract : In this article I analyse two of Marc Recha's films, Pau i el seu germà (2001 ) ['Pau and his Brother'] and Dies d'agost (2006 ) ['August Days'], attending closely to their inclusion of several scenes of male nudity which have received little critical coverage in existing scholarship. Even if nudity in the context of high-minded auteur cinema might be expected, its presence will always be conflictive due to the very nature of the spectatorship gaze, and thus demands closer consideration in terms of gender representation and approaches to masculinity in crisis. It will be argued that analysis of these scenes brings greater appreciation of Recha's subtle critique of heteronormative society and renders the male body yet another surface on which Recha engraves, at multiple levels, the trauma that painfully reverberates across all the bodies that populate his movies.